Nightmares in Medical Practice - Kalinchuk A. V., Antsyborov A. V. (Interactive science, 2020)
nightmares are scary or disturbing dreams which are associated with negative feelings, such as fear, terror or disgust. These feelings oftentimes awake the dreamer, who can easily recollect the content of the nightmare. Nightmares are not necessarily a symptom of a disease. Moreover, nightmares with little emotional response are experienced by almost all people once in a while without any risk for their health. However, nightmares that occur frequently and disturb the sleep might lead to clinically significant impairments in social, professional and other areas of life. They are considered a sleep disorder (parasomnia) and require a proper treatment. This review discusses the theoretical models of nightmares, their causes, diagnostics and treatment strategies.
Keywords: тревога; страх; fear; anxiety; травма; посттравматическое стрессовое расстройство; dream; nightmare; parasomnias; trauma; post-traumatic stress disorder; neurocognitive model; imagery rehearsal therapy; sleep-wake cycle; ночной кошмар; сновидение; парасомнии; нейрокогнитивная модель; цикл бодрствование-сон; образно-репетиционная терапия